MODEL STRATEGI PENGEMBANGAN DESA WISATA BERBASIS MASYARAKAT DI DESA KENDERAN, GIANYAR, BALI - Eka Mahadewi, Ni Putu; Sudana, I Putu (Jurnal Analisis Pariwisata, 2017)
Recently development of tourism in Gianyar regency is monotonous in the famous tourist attraction that there is no innovation to collaborate between the potential of nature, culture and creativity of the local community, thus raising the impression of similarity or similarity between tourist attractions with each other. One of the innovative breakthroughs that need to be done is through the development of Community Based Rural Tourism in Kenderan Village, Tegalalang District, Gianyar Regency. With this development is expected to improve quality life of the community, preserve the cultural arts of local communities and conserve the environment in a sustainable manner. Development of Rural Tourism in Kenderan Village, has a high selling value to be a leading tourist attraction, but the reality of this village has not been able to be developed as a professional rural tourism, both from aspects of management, human resources, and utilization of village potential. This research resulted to formulate several alternative strategies that can be applied in the development of Rural Tourism in Kenderan Village that is related to the aspect of destination, industry aspect, marketing aspect and institutional aspect.